From AI Tools to Language Mastery: Investigating the Contribution of Generative AI to Undergraduate Foreign Language Learning Outcomes (Beacon: International Journal of Education and Social Studies, 2025)
The integration of Generative Artificial Intelligence (AI) has transformed foreign language learning by providing learners with personalized, interactive, and adaptive learning experiences. This study investigates the contribution of Generative AI to foreign language learning outcomes among undergraduate students. Employing a mixed-methods research design, the study involved 93 participants consisting of foreign language learners and instructors from various higher education institutions. Quantitative data were collected through an online questionnaire, while qualitative data were obtained through semi-structured interviews. The quantitative findings revealed that students generally held positive perceptions of Generative AI, particularly regarding its contribution to overall language proficiency (M = 4.15), language skill development (M = 4.06), learner motivation and engagement (M = 4.01), and the ability to overcome language learning challenges (M = 3.90). Qualitative findings further identified five major themes: enhancement of language skills, increased learner motivation and engagement, personalized and adaptive learning experiences, pedagogical implications, and challenges associated with AI integration. The study concludes that Generative AI has significant potential to facilitate language mastery and improve foreign language learning outcomes in higher education. However, its successful implementation requires a balanced approach that combines technological innovation with effective pedagogical practices and ethical considerations.